2018
DOI: 10.1002/acm2.12400
|View full text |Cite
|
Sign up to set email alerts
|

SPECT/CT image‐based dosimetry for Yttrium‐90 radionuclide therapy: Application to treatment response

Abstract: This work demonstrates the efficacy of voxel‐based 90Y microsphere dosimetry utilizing post‐therapy SPECT/CT imaging and applies it to the prediction of treatment response for the management of patients with hepatocellular carcinoma (HCC). A 90Y microsphere dosimetry navigator (RapidSphere) within a commercial platform (Velocity, Varian Medical Systems) was demonstrated for three microsphere cases that were imaged using optimized bremsstrahlung SPECT/CT. For each case, the 90Y SPECT/CT was registered to follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Accurate absolute quantification of radiotracer distribution is essential for dosimetry aimed at personalized radionuclide therapy and may improve prediction of therapy response, prevention of toxicity effects, and treatment follow-up [1,2]. Both positron emission tomography (PET) and single-photon emission computed tomography (SPECT) hold the promise for absolute radioactivity quantification.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate absolute quantification of radiotracer distribution is essential for dosimetry aimed at personalized radionuclide therapy and may improve prediction of therapy response, prevention of toxicity effects, and treatment follow-up [1,2]. Both positron emission tomography (PET) and single-photon emission computed tomography (SPECT) hold the promise for absolute radioactivity quantification.…”
Section: Introductionmentioning
confidence: 99%
“…where A =activity, LSF = lung shunt fraction, T 1/2 = 90 Y half-life, E avg = average β-particle energy per disintegration (0.935 MeV), C voxel = counts within voxel, ΔV = voxel volume, ρ = tissue density, and C total = total counts within the patient [15]. The calculated dose in a given voxel is the voxel value divided by the total counts multiplied by a constant.…”
Section: Discussionmentioning
confidence: 99%
“…An assumption of the LDM model is that all the energy from β-particle decay is locally within the same voxel [15]. WFBH method uses a 5x5x5 scattering kernel to consider the effects on neighboring voxels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the positive predictive values, sensitivity, specificity and the accuracy of BS SPECT/CT were 100, 87, 100, and 99%, respectively ( 13 ). Furthermore, BS SPECT/CT after radioembolization is beneficial to evaluate tumor dose-response characteristics and predict treatment response for the management of patients ( 14 ). Potrebko et al.…”
Section: Yttrium-90mentioning
confidence: 99%